A Note on Studies on Nitrogen Requirement of Ttriticale under Rainfed Conditions - Ali, Masood; Rajput, P R (Annals of Arid Zone, 2016)
An investigation on the effect of doses and methods of nitrogen application on the yields of triticale grown on silty clay loam soil under rainfed and shallow water table conditions revealed that 60 kg N/ha significantly increased the number of spikes, number of grains/spike and grain and straw yields. Response beyond 60 kg N/ha was marginal. Application of nitrogen as basal or partly basal or partly basal and partly through foliage were on par.